2020
DOI: 10.3390/ijerph17228578
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Consequences of COVID-19 and Lockdown in the Spanish Population: An Exploratory Sequential Design

Abstract: The objectives of this study were to analyze the psychological impact of the COVID-19 pandemic and the lockdown in the Spanish population and to identify what population profiles were most affected. The study used a sequential exploratory design. In the qualitative phase, 40 participants were recruited based on theoretically relevant criteria and the saturation of the information provided by the interviews. In the quantitative phase, a large representative sample was applied. The universe considered was the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
23
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 31 publications
6
23
1
9
Order By: Relevance
“…Increased prevalence of MD and GAD after the outbreak was reported in some countries including Canada, China, and Greece [ 16 , 17 , 18 , 19 ]. Some epidemiologic studies assessing the impacts of COVID-19 outbreak on mental health outcomes [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] suggested that female gender, unemployment, poor self-reported health status, loneliness, poor social supports, and contact with suspected infection or COVID-19 confirmed cases were associated with greater risks of psychological distress from the pandemic. Identifying high-risk groups of mental health outcomes is imperative for developing psychological interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Increased prevalence of MD and GAD after the outbreak was reported in some countries including Canada, China, and Greece [ 16 , 17 , 18 , 19 ]. Some epidemiologic studies assessing the impacts of COVID-19 outbreak on mental health outcomes [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] suggested that female gender, unemployment, poor self-reported health status, loneliness, poor social supports, and contact with suspected infection or COVID-19 confirmed cases were associated with greater risks of psychological distress from the pandemic. Identifying high-risk groups of mental health outcomes is imperative for developing psychological interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic is one of very few social events to have had such an important impact on human psychology, especially due to the number of people affected and the influence it has had on all spheres of life [3]. All of this has led to a high level of psychological pressure on people in various countries [4,5], altering the mental health of adults, children, and adolescents and leading to changes in mood, behavior, and other daily habits, which may put the mental health of many people at risk both now and in the not-too-distant future [4,[6][7][8][9][10][11][12][13][14]. The pandemic and confinement has affected people of all characteristics; however, a specifically vulnerable group are children and adolescents with neurodevelopmental disorders such as Attention Deficit Hyperactivity Disorder (ADHD), and it is to be expected that the effects of confinement on their mental health will be more intense.…”
Section: Introductionmentioning
confidence: 99%
“…This was a higher compared to Norwegians in 2015, where 3.8% of men and 8.5% of women reported symptom-defined PTSD [ 13 ]. Women seem to be more sensitive to concerns and stress compared to men [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found three qualitative studies. Two-thirds of 40 Spanish informants [ 14 ] reported an increase in worrying about suffering from or contracting an illness (COVID-19 or other) relative to before the pandemic. Fear of losing loved ones increased in 76% and psychological distress such as sadness/depression, anxiety, anger and worrying were identified.…”
Section: Introductionmentioning
confidence: 99%